The role of maternal trauma and discipline types in emotional processing among Syrian refugee children - Peltonen Kirsi; Gredebäck Gustaf; Pollak Seth D; Lindskog Marcus; Hall Jonathan (Springer, 2022)
Stressful experiences in armed conflict incur intergenerational effects through parental behaviors with their children. A recent study reported that among Syrian refugee families, mothers' (but not fathers') post-traumatic stress (PTS) impacted children's emotional processing. In this study, we aim to shed further light on this phenomenon by analyzing how the parenting practices in the context of post-traumatic stress confers protection or risk for children's emotional processing. Participants were 6-18-year-old children (n = 212) and their mothers (n = 94), who fled from Syria and were residing in Turkish communities. We used the computer-based emotional processing task including photos of facial movements typically associated with different emotions to measure children's capacity for emotional processing. Mothers reported their PTS and the discipline types they use, as well as the contextual factors related to their refugee background. Linear mixed effect models were constructed first, to find out the discipline types that are most strongly associated with emotional processing of the child, and second, to examine whether these discipline types moderate the effect of maternal PTS on children's emotional processing. Finally, generalized linear models were constructed to examine which contextual factors are associated with the use of these discipline types by mothers. We found that spanking as a discipline type was associated with poorer child emotional processing, whereas withholding of media access was associated with better emotional processing. Younger and less religious mothers were more prone to use spanking. The study underlines the need for parenting programs alongside with efforts to address mental health issues among mothers living under armed conflict.